2022
DOI: 10.1186/s12978-022-01526-3
|View full text |Cite
|
Sign up to set email alerts
|

Typologies of women’s abortion trajectories in Burkina Faso: findings from a qualitative study

Abstract: Background Abortion is a legally restricted, yet common reproductive life event among women in Burkina Faso; however, women’s abortion experiences vary greatly depending on their social and economic capital, partner involvement, and level of knowledge. We sought to classify women’s abortion care-seeking experiences across the life course and social conditions into typologies using qualitative data. Methods An initial quantitative survey among a nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…One of the ways women seek information while avoiding public exposure is to involve their partners who do not face the same risk of social shame. As suggested in other studies conducted in legally restricted abortion settings [ 12 , 28 ], we found male partners take on much responsibility in women’s abortion trajectories, often connecting their pregnant partners directly to healthcare providers. However, in doing so, our results indicate some partners infringed on women’s reproductive autonomy, making decisions without sharing information.…”
Section: Discussionsupporting
confidence: 66%
“…One of the ways women seek information while avoiding public exposure is to involve their partners who do not face the same risk of social shame. As suggested in other studies conducted in legally restricted abortion settings [ 12 , 28 ], we found male partners take on much responsibility in women’s abortion trajectories, often connecting their pregnant partners directly to healthcare providers. However, in doing so, our results indicate some partners infringed on women’s reproductive autonomy, making decisions without sharing information.…”
Section: Discussionsupporting
confidence: 66%